Teaching Vocabulary under CLIL Approach in Indonesian Primary Schools: A Literature Review - Nuzul Hijrah Safitri; Aminah Maulidah Nugraha Silawati; Nurjannah; Sarniati Nuru (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This study sheds light on the roles of teachers and challenges they face in implementing CLIL approach in Indonesian primary schools since this approach has the feasibility to carry out at primary level. This study is a literature review that gains data related to the topic from journal articles and relevant books. This study reveals that teachers play a vital role in balancing the integration of content and language, designing a CLIL teaching materials and employing scaffolding vocabulary learning, a variety of vocabulary instruction and assessment. However, they face challenges such as limited English proficiency, cultural differences and contextual relevance, students’ motivation and engagement, the suitable teaching materials and resources, and assessment technique. Therefore, teachers are required to enhance their competences by participating in professional development programs, collaborating with colleagues, and seeking support from educational institutions and resources. This study provides insight to policy makers in Indonesia to provide the necessary support and resources to empower primary school teachers in effectively implementing the CLIL approach and fostering students' vocabulary development, leading to improved learning outcomes and the preparation of globally competent learners.